GeneHome – a Novel Model to Deliver Care to Individuals with Genetic Predisposition to Cancer. (15th June 2022) - Nocera Zachariah, Nadia; Lee, Marie C.; Chang, Maxine D.; Moore, Colin; Wang, Xia
Genetic testing for hereditary cancer predisposition is more widely available, resulting in more patients being identified as carriers of pathogenic variants (PV) of cancer susceptibility genes. PV carriers may be at high risk for multiple cancers of different organ systems. Traditional high-risk cancer screening is often organ specific and conducted separately by specialists. However, with many genes associated with 3 or more types of cancer risks, coordination of such cancer screening can be overwhelming for patients and providers. At Moffitt Cancer Center (MCC), GeneHome clinic functions as a "home" to conduct and coordinate prevention, screening, counseling, and education for individuals carrying germline genetic PVs across the entire spectrum of cancer genes. The screening includes, but is not limited to, history review, physical examination, image studies, blood tests, urine tests, and endoscopy. GeneHome is a novel model for genetic high-risk cancer surveillance and has grown in 4 years since establishment. We sought to study various characteristics of the patient population it serves, common themes in referral patterns and evolution of the clinic since its inception. A total of 821 patients were seen over 42 months, encompassing PV carriers of 46 genes. Patients were 84.9% female and 13.3% male. Most PVs were of BRCA1 and BRCA2 . Most patients had private insurance, and most were from Florida. Annual increase in patient visits was over 74.7% over the last year. Overall, GeneHome has been well accepted by providers and patients and is a valuable service for patients with a genetic predisposition to cancer.